John Falk and Lynn Dierking: building the field of informal/free-choice science education - Rennie, Leonie (2015)
This article establishes the importance of “context”, a concept that underpins the academic contributions that John Falk and Lynn Dierking have made in building the field of informal/free-choice learning in science education. I consider, in turn, the individual contributions made by each of them prior to their seminal co-authored work, entitled The Museum Experience. I then document their joint contributions to the field, pointing out that although their interests and skills overlap in complementary ways to produce their jointly authored works, both have continued to make their individual contributions; Falk in his work on identity and impact, and Dierking in her work on community, youth, family and equity. Finally I come to the present, describing how they each continue their research and publication in lifelong, life-wide, and life-deep learning, with a particular focus on free-choice learning and the role it can play in addressing critical issues in the world.